EFEKTIVITAS SISTEM PERADILAN SEDERHANA, CEPAT, DAN BIAYA RINGAN DI LINGKUNGAN PERADILAN UMUM - Sukolegowo, Pramono (Faculty of Law, Universitas Jenderal Soedirman, 2008)
Article 5 sentence ( 2) Law No. 4 Year 2004 concerning Judicial Power stated that the court help all searchers of justice and overcoming all barricade and resistance to reached the simple, quick, and light expense jurisdiction, so the system of judicature can be effective and efficient. There are some factors that influence the function of law in the society or make effectiveness of the law enforcement which are: substance of law, law enforcement, facility, and also society factor that the law environment applied. Keyword: Simple, quick, and Light Expense Jurisdiction